An Analysis of Jargon Used on Facebook Found in Account “Mark Zuckerberg” - Yuni Kartika; Ainur Rohmah; Dwi Andriani (Channing : Journal of English Language Education and Literature, 2020)
This study discusses An Analysis of Jargon Used on Facebook Found in account “Mark Zuckerberg”. Hopefully, this study useful for students of English Education, particularly to help them understand the jargon that is used in social media especially on Facebook. The goal of this study to find out the jargon used by "Mark Zuckerberg" in account Facebook. This analysis used the descriptive method because it is to describe the jargon meaning in the "Mark Zuckerberg" account on Facebook. The procedure of collecting the data are: (1) Reading and finding the status of “Mark Zuckerberg” account, (2) Identifying the jargon used in the status, (3) Marking and finding the meaning of jargon found in the status, and (4) Concluding the data analysis. Based on the finding, the writer found Fifteen jargons, ten jargons abbreviation, one jargon phrase, three jargon words, and one jargon acronym in the edition of January till May in 2020.